2011 debt limit crisis : how should the Fed respond? - English, William B. 1960- (SAGE Business Cases., 2019)
In July of 2011, the possibility that the US federal government would default on its debt was becoming an increasing likelihood. For Ben Bernanke, the Chair of the Federal Reserve System, breaching the debt limit was concerning. As the Treasury's fiscal agent, Bernanke and the Fed would advise the Treasury on how to pay its obligations. No matter how the Treasury chose to pay its obligations, the Fed's charge to regulate large money center banks and maintain stability in the financial markets would be put to a test. A Treasury default would mean that there would be large movements of cash and changes in perceptions of risk that could alter key financial ratios used to oversee bank operations. What guidelines should the Fed issue? To maintain financial stability, the Fed had a number of mechanisms at its disposal. Many of these related to existing desk operations that the Fed used to implement monetary policy, such as the sale and purchase of securities. But how should these be altered to deal with the influx of Treasury securities in default? The Fed staff also had prepared a number of novel courses of action that would help reduce strain and introduce increased liquidity. Should the Fed put these extraordinary measures into place?